2021
DOI: 10.1002/pen.25738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rheological and electrical percolation of high‐density polyethylene/carbon black composites using mathematical models

Abstract: In this work, conductive polymer composites (CPCs) of bio‐based polyethylene (BioPe) containing different concentrations of carbon black (CB) were developed. By using oscillatory rheology analysis, a Newtonian plateau was observed in BioPe, and all BioPe/CB composites had a behavior of a pseudo‐solid and that composites with volume fractions ranging from 0.24 to 0.56 presented higher viscosity, storage, and loss modulus. This suggests the formation of a percolated network and by using the power‐law models, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The decrease in the values of tan δ with increasing filler content coupling with the simultaneous shift of maximum tan δ to higher frequency regions suggested the transition of polymer melts from the viscous‐like state to solid‐like state, which is related to the structural change that induced by the formation of filler network 64,65 . Particularly, Figure 6c showed that the values of tan δ were almost independent of frequency for CBG, which indicated the construction of a well‐developed percolated filler network structure 66 …”
Section: Resultsmentioning
confidence: 89%
“…The decrease in the values of tan δ with increasing filler content coupling with the simultaneous shift of maximum tan δ to higher frequency regions suggested the transition of polymer melts from the viscous‐like state to solid‐like state, which is related to the structural change that induced by the formation of filler network 64,65 . Particularly, Figure 6c showed that the values of tan δ were almost independent of frequency for CBG, which indicated the construction of a well‐developed percolated filler network structure 66 …”
Section: Resultsmentioning
confidence: 89%
“…The critical volume fraction for achieving the percolation threshold is low for nanoparticles, which has been reported previously. [ 58,59 ] With a micrometer size particle‐like in the present PP gel systems, the critical percolation threshold volume reaches a plateau, and then increases slowly with particle size. At 16 wt% gel incorporation, assuming the constrained corona thickness is the same as in G2.5, G5, and G11, the effective volume fraction of G16 is equal to 51 vol%, which is close to the obtained percolation volume fraction.…”
Section: Discussionmentioning
confidence: 90%
“…This behavior indicates an increment in the viscoelastic characteristics of the nanocomposites caused by MWCNT. The Nylon 6/ABS/ABS-g-MA/MWCNT systems presented increased G’ values with increasing nanofiller content, mainly in the low-frequency region, which is typical of polymers loaded with conductive particles [ 55 , 56 ]. The nanocomposites containing 3 and 5 phr MWCNT presented higher G’ values than the sample with 1 phr MWCNT, following the same behavior observed for η*.…”
Section: Resultsmentioning
confidence: 99%